Menelusuri Jejak-jejak Kekerasan dalam Islam - Widodo, Sembodo Ardi (Unisia, 2010)
Islam is merely claimed as "violence religion". It may be true or false, or even it is just a "mythology". But It must be understood that, in fact, in the history of Islam, some kinds of violence have risen because of action of individual or group of Moslem by the name of Islamic religion. Beginning from scripturalism, from Qoran and Sunnah, the texts was understood and interpreted for the sake of action, created an aqidah and syari’ah, than created an attitude and behavior of life of Moslem; and because of it’s model of interpretation that faced to action and confronted with current condition and development of modern society in various aspects: political, social, cultural, and economical aspect, so militant Moslem groups rose against the unjustice actions, not only faced to another group with different religion but also to another Moslem group.